الامام محمد الفاضل بن عاشور (ت 1390هـ) وجهوده في التفسير وعلوم القرآن - جارالله, ساسية (University of Eloued جامعة الوادي, 2018)
بين دفتي هذا البحث دراسة حول جهود أحد أئمة المسلمين في خدمة القران الكريم ، وقد جاء موسوما بـ : (الإمام محمد الفاضل بن عاشور وجهوده في التفسير وعلوم القرآن). وقد تناولت الدراسة التعريف بشخصية الإمام محمد الفاضل بن عاشور من خلال استعراض ترجمة له، وكذلك إبراز جوانب من سيرته العلمية. كما حوت الدراسة في احد ثناياها الكلام عن كتابه التفسير وعلوم القرآن ورجاله وقد تضمنت الدارسة أيضا بيان جهود الإمام في ومن أبرز النتائج المتوصل إليها: أن الإمام محمد الفاضل بن عاشور من الشخصيات المتميزة في التاريخ الإسلامي، كما يعد كتابه التفسير وعلوم القرآن ورجاله من الكتب الهامة في مناهج المفسرين. This study includes a study on the efforts of one of the imams in the service of the Holy Quran, and it was referred to as: (Imam Muhammad al-Fadil bin Ashour and his efforts in interpretation and the sciences of the Koran). The study dealt with the definition of the personality of Imam Muhammad al-Fadhel bin Ashour through a review of his translation, as well as to highlight aspects of his biography. As the study whims in one of the words talk about his "Interpretation And His Men". The study also included a statement of the Imam's efforts in interpretation and the sciences of the Quran. The most prominent findings in this research is that Imam Muhammad al-Fadil ibn Ashour is one of the outstanding figures in Islamic history, and his book "Translation And His Men" is one of the important books of interpretation.
مذكرة ماستر تخصص تفسير وعلوم القرآن
Keywords: جهود، الامام محمد الفاضل بن عاشور، تفسير القرآن; Efforts, Imam Muhammad al-Fadil ibn Ashour, interprétation du Coran